SIFAT NUTRISIONAL PROTEIN RICH FLOUR (PRF) KORO PEDANG (Canavalia ensiformis L.) - Wiwik Siti Windrati; Ahmad Nafi’; Puspa Dewi Augustine (Faculty of Agricultural Technology, University of Jember, 2010)
Jack bean is one of beans which have 55% carbohydrate and 24% protein. It will make new market to explore jack bean as raw material component PRF (Protein Rich Flour). The aim of this research was to know the characteristic of PRF, including chemical and nutritional properties by using descriptive method. The results showed that jack bean PRF had 10,09% of water; 37,61% of protein; 4,49% of fat; 36,70% of starch (31,12% of amylose; 68,88% amylopectin); 0,57% of sugar; 2,23% of fiber and 3,04% of ash. The highest amino acid content is glutamic acid equal to 5,47%, while smallest is metionin equal to 0,32%; limiting amino acids are metionin and sistein equal to 8,51 mg/g protein; antitrypsin content 8,9% unit/g; 0,17 mg vitamine B1; 26,85 mg vitamine B2 and 56,16% of protein digestable by pepsin-trypsin enzyme.Keywords: Jack bean, protein rich flour, nutritional properties